Der Kaiser ist ein Lump und Spitzbube Majestätsbeleidigung unter Kaiser Franz Joseph - Czech, Philip (2010)
The subject of this study is the criminal prosecution of insulting remarks about the emperor in the Habsburg monarchy in the second half of the 19th century (1852-1918). The first chapter discusses the historical development of the protection of state and sovereign through penal law that resulted in the penal code of 1852. Then the norms on the protection of state and dynasty in this penal code and the settings of the criminal proceedings code are discussed. As lese majesty was a politically disputed matter, also the discussion on the planed reform of the penal code is given the necessary attention.The main part of the book examines which insulting remarks on Francis Joseph were in fact prosecuted by the Regional Court Salzburg. Special attention is paid to the question what motivated the defendants to insult the emperor and what conclusions can be drawn from their remarks regarding the relation between authority and subjects. In this context is also analyzed how the authorities got to know about the insulting remarks, which sentences where imposed by the Regional Court and from which factors the sentences where influenced. Also the social composition of the offenders is analyzed. On the basis of criminal statistics the study investigates, which social and political factors influenced the numbers of convictions for lese majesty. It can be demonstrated, how political and economic developments influenced public opinion and how on the other side the provision on lese majesty could be exploited to suppress political opposition. The last chapter is dedicated to the suppression of critical comments on the emperor and the dynasty in newspapers and other products of the press. Based on a description of the legal framework, the study analyzes how censorship was operated by the authorities in the crown-land Salzburg. The book shows which comments in newspapers lead to confiscations and which political developments or events within the royal family gave rise to critical comments.